Forced Hand: Educational Entrepreneurship and the COVID-19 Pandemic - Rybakova, Katie; Pare, Jeremy (Maine Policy Review, 2021)
Authors Katie Rybakova and Jeremy Pare share their perspectives on how the COVID-19 pandemic has affected their teaching experiences. They suggest ways to use the pandemic-induced changes in higher education to improve student experiences and outcomes.
Keywords: Maine; higher education; digital badges; remote learning